Hypoxic exposure to optimise altitude training adaptations in elite endurance athletes - Turner, G. (University of Brighton, 2016)
The purpose of this thesis was to examine the physiological and haematological responses to altitude training and hypoxic exposures. Furthermore to investigate if additional hypoxic exposure around a "live high-train high" altitude training camp could maximise adaptations. Study one provided a detailed insight into the current practices and perceptions of elite British endurance athletes and coaches to altitude training. A survey found that the athletes and support staff`s concerns included maintaining training load at altitude, reducing the acclimatisation period, maximising haematological adaptations and when to compete on return to sea level. These challenges were prioritised and investigated further in the thesis. Confidence in the optimised carbon monoxide (CO) rebreathing method (oCOR-method) is paramount when assessing haematological adaptations. Study two found that Radiometer ABL80 hemoximeter provided a more valid and reliable determination of percent carboxyhaemoglobin (%HbCO) with a minimum of three replicate blood samples to obtain an error of =1%. Study three found that administering different boluses of CO produced significantly different haemoglobin mass (tHbmass) results (0.6 mL·kg-1 = 791 ± 149 g; 1.0 mL·kg-1 = 788 ± 149 g; and 1.4 mL·kg-1 = 776 ± 148 g). A bolus of 0.6 to 1.0 mL·kg-1 provided sufficient precision and safety to determine %HbCO with the ABL80 hemoximeter. Additional hypoxic exposures have been identified as a strategy to maintain altitude haematological adaptations gained from altitude training camps. Study four investigated the time course of erythropoietin (EPO) and inflammatory markers after acute (2 h passive rest) hypoxic exposures (FiO2: 0.135, 0.125, 0.115, and 0.209). [EPO] increased in all hypoxic conditions 2 h post-exposure, being maintained until 4 h post-exposure, however, the largest increase came from the FiO2: 0.115 condition increasing by ~50% (P < 0.001). There were no differences found between hypoxic exposures in IL-6 or TNFa. Study five investigated the effect of acute hypoxia as a priming tool, by measuring the effect of increased circulating EPO on endurance performance. A 10 min pre-loaded treadmill running time trial (TT10) was preceded by 2 h normobaric hypoxia (HYPO; FiO2: 0.115), hyperoxia (HYPER; FiO2: 0.395) or normoxia (CON; FiO2: 0.209) 3.5 h prior to the TT10. No differences (P = 0.082) were found in distance covered during TT10 (HYPO: 2726 ± 277 vs. CON: 2724 ± 279 vs. HYPER: 2742 ± 281 m). Study six monitored physiological and haematological variables of elite endurance runners completing four weeks of live high-training high (LHTH; ~2,300 m) altitude training (ALT) compared to a control group (CON). A hypoxic sensitivity test (HST) was completed pre (PRE) and post-altitude (POST-2), alongside a treadmill test and oCOR-method. From PRE to POST-2 a difference in average lactate threshold (LT) (6.1 ± 4.6% vs. 1.8 ± 4.5%) and lactate turnpoint (LTP) (5.4 ± 3.8% vs. 1.1 ± 3.2%) was found within ALT, but not CON. Mean VO2max increased by 2.7 ± 3.5% in ALT, and decreased by 3.3 ± 6.3% in the CON group (P = 0.042). Total Hbmass increased by 1.9 ± 2.9% and 0.1 ± 3.3% (P > 0.05) from PRE to POST-2 in the ALT and CON group, respectively. No changes were found in mean tHbmass post-LHTH; however, EPO was lower at POST-1. The HST revealed desaturation at rest and hypoxic ventilatory response at exercise predicted individual changes in tHbmass and hypoxic cardiac response at rest predicted changes in VO2max. The evidence reported supports the notion that additional hypoxic exposures around an altitude training camp can maximise physiological and haematological adaptation via a prior understanding of an athlete`s response to hypoxia and therefore the optimisation the athlete`s altitude training needs.